Internationalisation strategies of hotels in the ASEAN region - Lugovaya, Evgeniya (2011)
The economic growth of the ASEAN region and its service industry in particular, is the primary reason of the growing interest of foreign investors in this region. Consequently, the rise of the Foreign Direct Investment (FDI) level results in the growth of Multinational Enterprises that establish operation in ASEAN. At the same time, the ASEAN is also experiencing growing popularity as a tourist destination. Due to the abovementioned facts, the current study’s research problem is to identify favourable conditions for international hotel sector development that will be beneficial for the economies of ASEAN countries. The current study involves investigation of the internationalisation strategies of hotels that expanded to the ASEAN region in order to identify reasons driving the decision of hotels to go international and to explain the choice of a particular location for the new operation establishment. In order to achieve these aims Dunning’s eclectic paradigm (1993) is employed, as it was found to be the most capable theory in terms of its ability to explain patterns of FDI. Based on the eclectic paradigm a set of factors that affect the ownership, location, and internalisation advantages of international hotels was identified and tested.The research conducted in the form of semi-structured interviews with hotel executives helped identify which particular factors have the most important effect on the competitive advantages, the location choice, and choice of entry mode of international hotels. These findings helped to achieve the research aims as well as to formulate recommendations for the governments of ASEAN countries regarding possible ways to improve the economic situation of the region.